Perkawinan di Bawah Umur dalam Keharmonisan Rumah Tangga di Desa Sukogidri Kecamatan Ledokombo Kabupaten Jember - Umar Faruq (LP3M INSTITUT KH YAZID KARIMULLAH, 2022)
This study aims to answer the resech problem that has been formulated in the formulation of the problem, that is 1) to reveal how the process of underage marriage in the village Sukogidri Ledokombo District, 2) What is the factor of underage marriage in the village Sukogidri Ledokombo District, and 3 ) What are the implications of underage marriage on domestic harmony. Research Methods with Approach and Type of Research is a qualitative approach with Field Research Type. Methods of data collection using observation, interviews, and documentation, and data analysis using data redaction techniques, display data and conclution drawing / verivication.. The analysis shows 1) the underage marriage process in Sukogidri village by inviting the community leaders, the nearest community, the families of the two brides, the father of mudin. The marriage process is done by the marriage contract by the community leader who has happened to resign the guardian from the bride's parent, 2) The occurrence of underage marriage in Sukogidri village is external factor, that is the insistence of the parents because of economic factor, worry about violating religion, and pregnant outside of marriage . And 3) the implications of underage marriage on household welfare have a negative impact. Negative impact is on the fulfillment of rights and obligations., In connection with this, in the household to be considered is the fulfillment of rights and obligations of husband and wife. Due to lack of preparedness in the household, the burden of rights and duties of husband and wife are still assisted by their respective parents. Creating a prosperous relationship in the family is not enough to be carried out by two husband and wife, it should involve all elements of the family, the readiness of the child in the household relationship still requires guidance and direction of the families of both parties, either from the wife or husband